2011
DOI: 10.1111/j.1365-2265.2011.04046.x
|View full text |Cite
|
Sign up to set email alerts
|

In anorexia nervosa, even a small increase in abdominal fat is responsible for the appearance of insulin resistance

Abstract: Although weight-recovery represents the main aim of treatment in AN, refeeding is associated with an increase in abdominal fat which might be responsible of the onset of insulin resistance. As BMI and weight-recovery were associated with impaired IS, they cannot be considered the only aim of treatment of AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
1
25
0
3
Order By: Relevance
“…In another DXA study, Mayer et al assessed body fat distribution in 29 women with anorexia nervosa and 15 age- and BMI-matched controls, finding no significant differences in percentage trunk fat between the two groups [14]. This was confirmed by Prioletta et al , who assessed regional body fat in 19 women with anorexia nervosa and 21 age-matched controls via DXA, and reported no difference in percentage trunk fat between the two groups [35]. Likewise, Grinspoon et al found no difference in trunk/extremity fat ratio between underweight young adult females with anorexia nervosa and healthy controls [32].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In another DXA study, Mayer et al assessed body fat distribution in 29 women with anorexia nervosa and 15 age- and BMI-matched controls, finding no significant differences in percentage trunk fat between the two groups [14]. This was confirmed by Prioletta et al , who assessed regional body fat in 19 women with anorexia nervosa and 21 age-matched controls via DXA, and reported no difference in percentage trunk fat between the two groups [35]. Likewise, Grinspoon et al found no difference in trunk/extremity fat ratio between underweight young adult females with anorexia nervosa and healthy controls [32].…”
Section: Resultsmentioning
confidence: 96%
“…More recently, Prioletta et al used DXA to assess regional body fat after a small weight gain in 19 females with anorexia nervosa and 21 age-matched controls (BMI from 13.6 ± 1.8 to 14.4 ± 1.1). They also found preferential redistribution of fat mass in the trunk region with respect to controls [35]. Similarly, we used DXA to measure body composition, in a larger sample of 50 women with anorexia nervosa and 100 healthy age- and BMI-matched controls [36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is scarce research focusing on short-and long-term effects of central fat changes on health-related parameters in AN-R patients, although excessive BF has been associated with risk for development of chronic and metabolic diseases [17]. However, one study has reported that small changes in central fat in AN patients were associated with a decreased insulin sensitivity, that could eventually result in an increased risk of developing metabolic and cardiovascular-related diseases [40].…”
Section: Discussionmentioning
confidence: 98%